2020
DOI: 10.1002/suco.201900166
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of synergetic effect on microscopic and mechanical properties of steel‐polypropylene hybrid fiber reinforced concrete

Abstract: Fiber reinforced concrete (FRC) is presently being replaced with plain concrete for its superior performance. In most cases, FRC contains just a single kind of fiber. The utilization of at least two kinds of fibers in an appropriate mix can possibly improve the mechanical properties of concrete and result in performance synergy. This paper explores the effect of using steel fiber and polypropylene fiber for reinforcing the concrete to quantify the mechanical properties of the concrete composite. The purpose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 37 publications
(40 reference statements)
1
6
0
Order By: Relevance
“…These deformations prevent slippage and allow maximum utilization of the tensile force. The same improvement in (ffRC) due to fiber reinforcement has been reported previously [58,64]. Similar to the shear strength test, the 3-point bending test observed the significant effect of recycled fibers on increased flexural tensile strength.…”
Section: Flexural Strength Test Resultssupporting
confidence: 85%
“…These deformations prevent slippage and allow maximum utilization of the tensile force. The same improvement in (ffRC) due to fiber reinforcement has been reported previously [58,64]. Similar to the shear strength test, the 3-point bending test observed the significant effect of recycled fibers on increased flexural tensile strength.…”
Section: Flexural Strength Test Resultssupporting
confidence: 85%
“…Polypropylene (PP) is the second most used polymer; it exhibits excellent chemical resistance, facile processability through different techniques (such as injection and extrusion), and low-cost production, which in turn makes it a versatile option for several industries, such as construction, [1][2][3] automobiles, 4 food packaging 5 and others. [6][7][8] There are some drawbacks that limit the wider use of PP, such as high flammability, low tensile strength and low impact resistance, and it is a poor barrier for O 2 gas.…”
Section: Introductionmentioning
confidence: 99%
“…However, owing to the brittleness and lack of flexural/tensile strength of cementitious materials, many studies have focused on improving its mechanical strength. The typical method for improving the flexural/tensile strength of cementitious materials is to employ fibers such as polypropylene fiber, carbon fiber, steel fiber, and glass fiber as reinforcing agents [ 2 , 3 , 4 , 5 , 6 ]. Xue et al [ 7 ] and Cao et al [ 8 ] reported that the fiber exhibited various reinforcement effects on cementitious materials due to their different types and lengths.…”
Section: Introductionmentioning
confidence: 99%